Ergometer training volume and previous injury predict back pain in rowing; strategies for injury prevention and rehabilitation - Wilson, F.; Gissane, C.; McGregor, A. (British Journal of Sports Medicine, 2014)
The most commonly reported injury site in rowers is the lower back. Research in recent years has focused on epidemiology and biomechanical analyses to try and understand mechanisms that contribute to this injury's onset. Injury surveillance mainly comprises retrospective questionnaires and reviews of medical records with a lack of prospective data. Of studies that reported 12-month data, the incidence of low back pain ranged from 31.8 to 51% of the cohort. Of the limited studies that specifically examined low back pain in rowers, (1) history of lumbar spine injury and (2) volume of ergometer training were the most significant risk factors for injury onset. Studies of technique on the rowing ergometer have indicated the importance of lumbopelvic rotation during rowing. Greater pelvic rotation at either end of the stroke is ideal—as opposed to lumbar flexion and extension; this tends to be poorly demonstrated in novice rowers on ergometers. Furthermore, technique can deteriorate with the demands of rowing intensity and duration, which puts the rower returning from injury at additional risk.